Efficacy of Combined Analogy and Demonstration Methods of Teaching on Students' Academic Performance in Basic Technology - Wada, B. Zira (International Journal of Educational Management, 2021)
This study examine the efficacy of combined analogy and demonstration methods of teaching on students' academic performance in Basic technology. A quasiexperimental pre-test post test non equivalent control group was adopted. The total number of students in the class was considered. The schools were randomly assigned to one of the two groups. Two research questions and two hypotheses were raised and the data collected were analysed using Welch and homogeneity test while the hypotheses were tested using Analysis of Variance (ANOVA) at 0.05 level of significance. It was therefore concluded based on the results that Basic Technology is better understood when taught using combined analogy and demonstration method of teaching the conventional lecture method. It was therefore recommended among others that Basic technology should be taught using combined analogy and demonstration method of teaching.